Ca Distribution Pattern in Litchi Fruit and Pedicel and Impact of Ca Channel Inhibitor, La3+ - Wen-Pei Song; Wei Chen; Jun-Wen Yi; Hui-Cong Wang; Xu-Ming Huang (Frontiers in Plant Science, 2018)
Calcium (Ca) deficiency in fruit causes various physiological disorders leading to quality loss. However, disorders related to Ca deficiency are not simply caused by a shortage of calcium supply. Ca distribution is also an important relation. This study examined Ca distribution pattern in fruit and pedicel in litchi (Litchi chinensis Sonn.) and the influence of Ca channel inhibitor La3+ on fruit Ca uptake and distribution. In situ distribution of Ca in the phloem and xylem tissues of the pedicel was visualized by Ca mapping with X-ray microanalyzer. Ca2+ analogy Sr2+ was used to trace Ca2+ transport pathway to fruit as well as distribution pattern. The results showed Ca was more distributed in the pericarp, especially the distal part. Ca level in the bark/phloem was always significantly higher than in the xylem and increased with stem age, suggesting constant influx of Ca into the phloem from the xylem. La3+ increased the ratio of Ca in the xylem to that in the bark in the pedicel and significantly reduced Ca accumulation by 55.6% in fruit, suggesting influx of Ca into the symplast was involved in fruit Ca uptake. Sr2+ introduced from fruit stalk was found to be transported to fruit through the phloem as Sr was largely distributed in the phloem, and fruit stalk girdling significantly reduced Sr accumulation in the pericarp. Ca mapping across the pedicel revealed Ca-rich sites in the parenchyma cells in the phloem and along the cambium, where abundant Ca oxalate crystals were found. The results suggested extensive influx of Ca from xylem/apoplast pathway into the phloem/symplast pathway in the pedicel, which enables phloem/symplast pathway to contribute a considerable part to Ca uptake in litchi fruit.